IMPACT OF INTEGRATED REPORTING ON FIRM VALUE: SYSTEMATIC LITERATURE REVIEW EVIDENCE FROM ASIA - Praditya, Krisna; Yusnaini, Yusnaini (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study aims to analyze the impact of Integrated Reporting on firm value in various industries, both domestically and internationally, that have already adopted Integrated Reporting. The theory used in this study is called the stakeholder theory.Methods: This study examines 20 articles from the 2019–2024 study period, out of 999 articles retrieved from the Scopus, Sinta, and Google Scholar databases using the Publish or Perish software.Results: The study shows differences between a few studies on the impact of integrated reporting on firm value. The majority of respondents indicate that there is a positive impact of integrated reporting on firm value. Keywords: Firm value, Integrated reporting, Systematic literature review